SEMINARI TINGGI MAZMUR 21 KALIMANTAN BARAT - Tendiono, Michael Vica; Khaliesh, Hamdil; Caesariadi, Tri Wibowo (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2022)
Seminary is a place for Christian religious education to form and educate prospective Christian clergy. The seminary is equipped with various educational support facilities, because it is a special education that focuses on theological/religious education. Seminary facilities in the Pontianak City area are currently considered to be less than optimal, both in terms of quantity/quantity, and quality of facilities. The purpose of this design is to produce the design of educational facilities and religious tourism that is able to accommodate the needs of users and visitors in the form of facilities and infrastructure. The design object focuses on the Bukit Doa Psalm 21 area, Anjongan, Mempawah. The method used in this design is observation, comparison, and analysis. The author will conduct field observations at seminaries and retreat houses in Pontianak, as well as interviews with related parties. The design focus is on identifying seminary facilities and the need for infrastructure. The theme that will be focused on this design is contextual architecture which focuses on linking new buildings with the environment. References to contextual architecture and similar buildings are taken from various sources. The collected case studies will later become a design guide, ideas and solutions to design problems. The seminary design concept is in the form of a spatial program schematic and site analysis which results in the identification of the required facilities and a schematic design of the seminary area and building. The final result of the design of the West Kalimantan Psalm 21 High Seminary is the the seminary area and building that has complete infrastructure that is able to accommodate educational activities and religious tourism, but also has a connection with the surrounding environment.